Fisher Scientific : (Fisher Scientific B. V., 2001)
The Fisher Web Site is your online ordering source for quality labware, dependable instruments and some of the most innovative tools in the market. Provider of apparatus and reagents for scientific laboratories and industry. Posts online ordering instructions, a corporate phone/e-mail directory, and listings of offices worldwide. Offers information on employment opportunities with the company. Links to searchable product catalogs, including "Fisher Catalog," "Fisher Chemical Catalog," "Fisher BioReagents," and "ACROS Organics.